Luciferase-based reporter to monitor the transcriptional activity of the SIRT3 promoter - Satterstrom, F. Kyle (Methods Enzymol, 2014)
Sirtuin 3 (SIRT3) is a major regulator of oncometabolism. Its activity or lack thereof significantly affects cellular oxidative stress, glycolytic gene expression, and tumorigenic potential. Thus, a system to accurately measure the level of SIRT3 transcriptional activation could lead to the identification of new cancer therapies and may have diagnostic applications. Here, we describe the development of a luciferase-based plasmid reporter system to measure activation of the human SIRT3 promoter. We detail the steps involved in construction of the system, including primer design, promoter fragment amplification, cloning, bacterial transformation, and mutagenesis. We validate this system in human 293T cells using the known activation of the SIRT3 promoter by the transcription factor estrogen-related receptor α, and we further show novel activation by the small molecule rapamycin, which has been used as a calorie restriction mimetic. Finally, we give an overview of the complementary molecular biology techniques that may be used to verify the results of this system.